A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMP N 1 KUBU IN COMPREHENDING NARRRATIVE TEXTS - Cica Umira; Fadly Azhar; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aimed to describe Student’s ability in compehending narrative text of the second year students of SMPN 1 Kubu. This descriptive research took place in SMP N 1 Kubu from April-Mei 2017. The population were about 90 students. The characters of the population are homogen in term of academic and age factors. The sample consisted of two clases, try out classs and sample class. Try out class consisted of 30 students and 30 students from sample class. In this research,the try out test aimed at acknowledging the validity of the test. The cluster random strategies technique was choosen due to that every class has equal ooportunity to be a sample group. The time allocation to administer the try out test and the revised test was 60 minutes for each of them. The data were analyzed by calculating the students’ score individually and finding out the mean of the score. The students’ scores were classified into five level mastery. They are: very poor, poor, mediocre, good and excellent. Based on the data analysed of this research, the students’ ability in comprehending narrative text at second year students of SMP N 1 Kubu was in mediocre level. Meanwhile, the mean score of the whole students’ scores was 59. The implication of the finding is that the second year students of SMP N 1 Kubu were able enough at comprehen narrative text.Key Word : Students’ Ability, Comprehending Narrrative Texts